Compressed Informativeness in Polish Legal Text - Kowalczyk, Joanna (Respectus Philologicus, 2022)
The present paper focuses on one of the main features of legal communication, namely informativeness. The article presents the informativeness of Polish legislative documents as an inherent but not always clearly understood socially feature of legal discourse, which has been regarded as a distinctive characteristic of normative acts. The study includes several levels of approximate semiotisation in relation to the cognitive criterion. The corpus comprises the most important Polish normative texts, namely the Constitution of the Republic of Poland, Criminal Code, Civil Code, and the Code of Civil Procedure. The analysis also included rulings of Polish common courts. Pragmatic and semantic criterion has been applied as the methodological basis for the analysis. The factor related to the use of legislative metaphors in executive and judicial practice was applied as an additional criterion. The aim of the paper was to determine the form of informativeness of the Polish legal texts and its extra-textual usefulness. Two levels of informativeness of legal texts, surface level and deep level, were established in the analysis. In legal discourse, informativeness took the form of a specific phenomenon. It referred not only to surface structures, but also to the elements of the content, requiring reconstruction from their meaning.
Keywords: normative text; semantics; legal education; legal provisions